Clarifying the evidence for microbial‐ and plant‐derived soil organic matter, and the path toward a more quantitative understanding - Emily D. Whalen; A. Stuart Grandy; Noah W. Sokol; Marco Keiluweit; Jessica Ernakovich; Richard G. Smith; Serita D. Frey (Global Change Biology, 2022)
Predicting and mitigating changes in soil carbon (C) stocks under global change requires a coherent understanding of the factors regulating soil organic matter (SOM) formation and persistence, including knowledge of the direct sources of SOM (plants vs. microbes). In recent years, conceptual models of SOM formation have emphasized the primacy of microbial‐derived organic matter inputs, proposing that microbial physiological traits (e.g., growth efficiency) are dominant controls on SOM quantity. However, recent quantitative studies have challenged this view, suggesting that plants make larger direct contributions to SOM than is currently recognized by this paradigm. In this review, we attempt to reconcile these perspectives by highlighting that variation across estimates of plant‐ versus microbial‐derived SOM may arise in part from methodological limitations. We show that all major methods used to estimate plant versus microbial contributions to SOM have substantial shortcomings, highlighting the uncertainty in our current quantitative estimates. We demonstrate that there is significant overlap in the chemical signatures of compounds produced by microbes, plant roots, and through the extracellular decomposition of plant litter, which introduces uncertainty into the use of common biomarkers for parsing plant‐ and microbial‐derived SOM, especially in the mineral‐associated organic matter (MAOM) fraction. Although the studies that we review have contributed to a deeper understanding of microbial contributions to SOM, limitations with current methods constrain quantitative estimates. In light of recent advances, we suggest that now is a critical time to re‐evaluate long‐standing methods, clearly define their limitations, and develop a strategic plan for improving the quantification of plant‐ and microbial‐derived SOM. From our synthesis, we outline key questions and challenges for future research on the mechanisms of SOM formation and stabilization from plant and microbial pathways.